2017
DOI: 10.4152/pea.201703159
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Studies on the Corrosion Inhibition Potentials of Two Tetrakis Pyrazole Derivatives for Mild Steel in 1.0 M HCl

Abstract: The inhibition performance and mechanism of N 1 ,N 1 ,N 3 ,N 3 -tetrakis((3,5-dimethyl-1H-pyrazol-1-yl)methyl)propane-1,3-diamine (BF2) and N 1 ,N 1 ,N 2 ,N 2 -tetrakis((3,5-dimethyl-1H-pyrazol-1-yl)methyl) benzene-1,2-diamine (BF4) for the corrosion of mild steel in 1.0 M HCl were investigated using weight loss method and electrochemical measurements. The results show that both tetrakis pyrazole derivatives act as good inhibitors, and inhibition efficiency follows the order: BF4 > BF2. Two tetrakis pyrazole d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…It can be observed that from Fig. 3, both the cathodic and anodic reactions were suppressed with the addition of inhibitor, which suggested that the inhibitor studiedreduced anodic dissolution and also retarded the hydrogen evolution reaction [7]. Table 3.…”
Section: Potentiodynamic Polarization Curvesmentioning
confidence: 87%
See 2 more Smart Citations
“…It can be observed that from Fig. 3, both the cathodic and anodic reactions were suppressed with the addition of inhibitor, which suggested that the inhibitor studiedreduced anodic dissolution and also retarded the hydrogen evolution reaction [7]. Table 3.…”
Section: Potentiodynamic Polarization Curvesmentioning
confidence: 87%
“…Table 3. It can be observed that from (Figure 3), both the cathodic and anodic reactions were suppressed with the addition of inhibitor, which suggested that the inhibitor studiedreduced anodic dissolution and also retarded the hydrogen evolution reaction [7]. The corrosion potentials (E corr ) for the mild steel in the presence of aqueous extract are slightly shifted toward the positive potentials compared with the mild steel in 1.0 M HCl.…”
Section: Potentiodynamic Polarization Curvesmentioning
confidence: 92%
See 1 more Smart Citation
“…Table 1 listed the corrosion rate values and the efficiencies of the inhibitions for each concentration, it is clear that 1,1´-(pyridine-2,6-dihylbis(methylene))bis(5-methyl-1-Hpyrazole-3-carboxylic acid) showed a best inhibitive effect, the efficiency reach until 93% in HCl 1 M medium at 10 -3 mol/l. This result could be explain by the fact that the adsorption coverage increases with the increase of inhibitor´s concentration, which shields the mild steel surface efficiently from the medium [5]. …”
Section: Weight Loss Measurementsmentioning
confidence: 92%
“…In order to search for new corrosion inhibitors in various acid media, our laboratory has published several works [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%